2021
DOI: 10.1038/s41598-021-91907-8
|View full text |Cite
|
Sign up to set email alerts
|

Y disruption, autosomal hypomethylation and poor male lung cancer survival

Abstract: Lung cancer is the most frequent cause of cancer death worldwide. It affects more men than women, and men generally have worse survival outcomes. We compared gene co-expression networks in affected and unaffected lung tissue from 126 consecutive patients with Stage IA–IV lung cancer undergoing surgery with curative intent. We observed marked degradation of a sex-associated transcription network in tumour tissue. This disturbance, detected in 27.7% of male tumours in the discovery dataset and 27.3% of male tumo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…According to the GO analysis, in men with MMD, many sex-specific DEGs take part in the bioprocess of DNA methylation. A previous study has reported that hypomethylation of a specific promoter CpG site of sortilin 1 in endothelial colony-forming cells from MMD was related to endothelial cell function, implying the involvement of hypomethylation of sortilin 1 in MMD pathogenesis (Sung et al, 2018 ) Recently, a study reported that men with lung cancer showed extensive autosomal DNA hypomethylation and a significantly increased risk of death (Willis-Owen et al, 2021 ). This result indicates that the level of aberrant DNA methylation in men and women may lead to a different pathophysiology of MMD.…”
Section: Discussionmentioning
confidence: 99%
“…According to the GO analysis, in men with MMD, many sex-specific DEGs take part in the bioprocess of DNA methylation. A previous study has reported that hypomethylation of a specific promoter CpG site of sortilin 1 in endothelial colony-forming cells from MMD was related to endothelial cell function, implying the involvement of hypomethylation of sortilin 1 in MMD pathogenesis (Sung et al, 2018 ) Recently, a study reported that men with lung cancer showed extensive autosomal DNA hypomethylation and a significantly increased risk of death (Willis-Owen et al, 2021 ). This result indicates that the level of aberrant DNA methylation in men and women may lead to a different pathophysiology of MMD.…”
Section: Discussionmentioning
confidence: 99%
“…KDM5D, recognized as a sexually dimorphic gene, is 85% identical to KDM5C and more frequently encoded in the Y chromosome of all male tissues. 34,35 Here, we deciphered that KDM5D gene mutations were prominently lower than other KDM5 members in NSCLC. Higher KDM5D expression led to a reduced FP and OS in LUAD and LUSC patients, regardless of the lymphatic metastasis status.…”
Section: Dovepressmentioning
confidence: 97%
“…KDM5D, encoded on the Y chromosome, has recently been shown to be a tumor suppressor gene. The incidence of ccRCC and lung cancer is higher in men than in women, and men have poorer outcomes [147,148]. Importantly, the total or partial loss of the Y chromosome, including the KDM5D locus, has been observed not only in prostate cancer but also in ccRCC and lung cancer in males, and lower KDM5D expression is associated with poor prognosis [147][148][149][150].…”
Section: Kdm5dmentioning
confidence: 99%